2023
DOI: 10.1155/2023/5911546
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐182‐5p Targets FGF9 to Alleviate Osteoarthritis

Abstract: Background. The pathogenesis of osteoarthritis (OA) is complex and there is no specific drug for treatment. The aim of this study was to identify the molecular targets of OA therapy, focusing on the expression and biological functions of miR-182-5p and its target genes in OA. Methods. miR-182-5p and fibroblast growth factor 9 (FGF9) were overexpressed or knocked down in IL-1β-induced chondrocytes. An OA knee model was performed by surgically destroying the medial meniscus. The gene expression of miR-182-5p and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Studies have shown that CC can treat a variety of arthritis, and it is better for OA, RA and GA. CC has the characteristics of multiple components, multiple targets, and multiple pathways in the treatment of arthritis. Currently, IL-10, IL-1β, IL-6, MMP-3, TNF-α and other targets have been verified to play a role in treating arthritis by CC ( Table 2 ) ( Sun et al, 2011 ; Yuan et al, 2014 ; Kienhorst et al, 2015 ; Huang et al, 2019 ; Thomas, 2020 ; Che et al, 2021 ; Li et al, 2021 ; Wu et al, 2021 ; Arra et al, 2022 ; Zhang et al, 2022 ; Cao et al, 2022 ; Du et al, 2022 ; Pacifici, 2022 ; Wirth et al, 2022 ; Xiao et al, 2022 ; Yang et al, 2022 ; Sun et al, 2023a ; Barbarroja et al, 2023 ; Li et al, 2023 ; Brix et al, 2023 ; Wang et al, 2023b ; Wang et al, 2023 ; Ghosh et al, 2023 ; González-Chávez et al, 2023 ; Hecquet et al, 2023 ; Jahantigh et al, 2023 ; Ji et al, 2023 ; La Bella et al, 2023 ; Leung et al, 2023 ; Lin et al, 2023 ; Luo et al, 2023 ; Zeng et al, 2023 ; Zhang et al, 2023 ). However, the types of arthritis treated with these targets are not completely clear.…”
Section: Deep Exploration Based On Potential Therapeutic Targets For ...mentioning
confidence: 99%
“…Studies have shown that CC can treat a variety of arthritis, and it is better for OA, RA and GA. CC has the characteristics of multiple components, multiple targets, and multiple pathways in the treatment of arthritis. Currently, IL-10, IL-1β, IL-6, MMP-3, TNF-α and other targets have been verified to play a role in treating arthritis by CC ( Table 2 ) ( Sun et al, 2011 ; Yuan et al, 2014 ; Kienhorst et al, 2015 ; Huang et al, 2019 ; Thomas, 2020 ; Che et al, 2021 ; Li et al, 2021 ; Wu et al, 2021 ; Arra et al, 2022 ; Zhang et al, 2022 ; Cao et al, 2022 ; Du et al, 2022 ; Pacifici, 2022 ; Wirth et al, 2022 ; Xiao et al, 2022 ; Yang et al, 2022 ; Sun et al, 2023a ; Barbarroja et al, 2023 ; Li et al, 2023 ; Brix et al, 2023 ; Wang et al, 2023b ; Wang et al, 2023 ; Ghosh et al, 2023 ; González-Chávez et al, 2023 ; Hecquet et al, 2023 ; Jahantigh et al, 2023 ; Ji et al, 2023 ; La Bella et al, 2023 ; Leung et al, 2023 ; Lin et al, 2023 ; Luo et al, 2023 ; Zeng et al, 2023 ; Zhang et al, 2023 ). However, the types of arthritis treated with these targets are not completely clear.…”
Section: Deep Exploration Based On Potential Therapeutic Targets For ...mentioning
confidence: 99%